2014
DOI: 10.1097/meg.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Major hepatectomy is safe for hepatocellular carcinoma in elderly patients with cirrhosis

Abstract: With rigorous screening of patients and improvement of perioperative management and operative techniques, major hepatectomy can be safely performed on HCC patients aged 70 years or more with liver cirrhosis. Intraoperative red blood cell transfusion of 5 U or more was predictive of higher morbidity in the elderly. Surgeons should take care to minimize the likelihood of intraoperative blood transfusion in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…As a result of recent advances, liver resection has become a reasonably safe treatment, and aggressive surgical resection has been proposed for cases with advanced disease [30][31][32]. Consequently, the age of patients undergoing liver resection has recently been increasing [33,34]. This situation indicates the emerging need for a formula that includes age in predictions of the SLV [4].…”
Section: Discussionmentioning
confidence: 96%
“…As a result of recent advances, liver resection has become a reasonably safe treatment, and aggressive surgical resection has been proposed for cases with advanced disease [30][31][32]. Consequently, the age of patients undergoing liver resection has recently been increasing [33,34]. This situation indicates the emerging need for a formula that includes age in predictions of the SLV [4].…”
Section: Discussionmentioning
confidence: 96%
“…The operation time, American Society of Anesthesiologists (ASA) physical status classification, blood transfusion and other factors have been reported to contribute to post-operative morbidity (26,27). A score based on age, presence of cardiovascular disease, pulmonary disease and diabetes mellitus, as well as performance status and the ASA score, can be used to predict post-operative morbidity (28).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , many recent studies have reported that surgical outcomes among older patients with HCC were comparable with those among younger patients with HCC. For elderly patients with HCC, the mortality rate after hepatectomy ranged from 0 to 42.9% while the morbidity rate ranged from 9 to 51%.…”
Section: Increasing Liver Resection In Elderly Patientsmentioning
confidence: 89%